1997
DOI: 10.1021/ie9701940
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modeling of Kraft Delignification of Eucalyptus globulus

Abstract: A kinetic model for the kraft pulping delignification of Eucalyptus globulus is proposed. This model is discriminated among some kinetic expressions often used in the literature, and the kinetic parameters are determined by fitting of experimental results. A total of 25 isothermal experiments at liquor-to-wood ratios of 50 and 5 L kg -1 have been carried out. Initial, bulk, and residual delignification stages have been observed during the lignin removal, the transitions being, referring to the lignin initial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
56
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 6 publications
11
56
1
Order By: Relevance
“…This activation energy is within the range 64 -96 kJ/mol found correspondingly for the initial, bulk and residual lignin fractions (Shatalov and Pereira 2005). This value is in line with the range of 40 -80 kJ/mol reported for wood kraft delignification (Santos et al 1997) and of 66 -78 kJ/mol reported for acetic acid pulping of E. globulus (Va´zquez et al 1995). Nevertheless, it is substantially lower than that found for other organosolv processes such as methanol-water based pulping of black cottonwood (96 kJ/mol) or acid-catalysed fractionation of wheat straw (128 kJ/mol) found from similar statistical analyses (Tirtowidjojo et al 1988;Siridas and Koukios 2004).…”
Section: Model Parameters For the Delignification Kineticssupporting
confidence: 89%
“…This activation energy is within the range 64 -96 kJ/mol found correspondingly for the initial, bulk and residual lignin fractions (Shatalov and Pereira 2005). This value is in line with the range of 40 -80 kJ/mol reported for wood kraft delignification (Santos et al 1997) and of 66 -78 kJ/mol reported for acetic acid pulping of E. globulus (Va´zquez et al 1995). Nevertheless, it is substantially lower than that found for other organosolv processes such as methanol-water based pulping of black cottonwood (96 kJ/mol) or acid-catalysed fractionation of wheat straw (128 kJ/mol) found from similar statistical analyses (Tirtowidjojo et al 1988;Siridas and Koukios 2004).…”
Section: Model Parameters For the Delignification Kineticssupporting
confidence: 89%
“…This period is known as initial st period or bulk stage a minor value of k (3x10 -4 min -1 ) w in the reaction rate corresponds to the removal of inte ones of the fibers. Finally, the residual stage showed min -1 ) due to that during this stage the lignin content in ese delignification stages were similar to those reported globulus [12] and several hardwoods when using a K mical reaction kinetic and delignification stages iption of the pulping process, the microstructural stud gnification kinetic process. Figure 2 shows the microstr erved under CLSM and SEM, for selected cooking tim SM images where two spectral channels can be simu ere the green color corresponds to lignin autofluorescen ked with the fluorescence of calcofluor used for cellul the kinetic (0 min) the fluorescence of the cellulose was the lignin autofluorescence was very intense.…”
Section: Cussion Hanges During Delignification Kineticssupporting
confidence: 80%
“…Descriptive statistics and linear regressions were done for all experiments and for the image analysis results the normal distribution of the data (Shapiro-Wilk Kolmogorov-Smirnov) was performed to determine using the statistical program Sigmaplot version 12.0 (Systat software Inc., USA). Figure 1 shows the delignif as catalyzer with the three be associated to a high rea moval of superficial lignin [12]. Regarding the second obtained.…”
Section: Linear Prediction Models For Delignification and Statisticalmentioning
confidence: 89%
“…In the terminal stage or residual period, the cleavage of carbon-carbon bonds in lignin molecule as well as carbohydrate degradation occurs. 27,28 Lignin removal or dissolution rate could be expressed as a first-order mechanism…”
Section: Kinetics Of Delignificationmentioning
confidence: 99%